Exploring entrepreneurial literacy knowledge transfer among women farmers group - Citra Ayni Kamaruddin; Muhammad Hasan; Nur Arisah (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2024)
Purpose — This research aims to explore the entrepreneurial literacy possessed by the women farmers group.Method — This research employs a qualitative approach utilizing a case study method specifically focused on the women farmers group. The informants in this study consist of two individuals from the women farmers group in Buntusu District, Tamalanrea Regency, namely the Chair and Secretary. Data collection techniques include observation and interviews. Data analysis involves testing data validity through time triangulation and reflexivity processes.Result — The findings of this study demonstrate four dimensions essential for assessing entrepreneurial literacy within the women farmers group. These dimensions encompass: (1) decision-making proficiency, (2) adeptness in selecting viable business strategies, (3) competence in managing and allocating financial resources, and (4) proficiency in transforming agricultural outputs into commercially viable products.Practical implications — This study serves as a basis for the development of government policies aimed at empowering women farmers group to enhance the productivity of urban land for agricultural purposes, meeting the community's needs, particularly for food products.